Muscle strength in youth and cardiovascular risk in young adulthood (the European Youth Heart Study). Issue 2 (23rd March 2013) - Grøntved, Anders; Ried-Larsen, Mathias; Møller, Niels Christian; Kristensen, Peter Lund; Froberg, Karsten; Brage, Søren; Andersen, Lars Bo
Abstract : Background: Whether muscle strength in youth is related to cardiovascular risk later in life independent of cardiorespiratory fitness is unclear. Methods: We examined the independent association of isometric muscle strength in youth with cardiovascular risk factors in young adulthood using data from the Danish European Youth Heart Study; a population-based prospective cohort study among boys and girls (n=332) followed for up to 12 years. In youth maximal voluntary contractions during isometric back extension and abdominal flexion were determined using a strain-gauge dynamometer and cardiorespiratory fitness was obtained from a maximal cycle ergometer test. Cardiovascular risk factors were obtained in youth and in young adulthood. Associations were examined using multivariable-adjusted regression models including major confounding factors. Results: Each 1 SD difference in isometric muscle strength in youth (0.17 N/kg) was inversely associated with body mass index (BMI; −0.60 kg/m 2, 95% CI −0.97 to −0.22), triglyceride (−0.09 mmol/l, 95% CI −0.16 to −0.02), diastolic blood pressure (BP) (−1.22 mm Hg, 95% CI −2.15 to −0.29) and a composite cardiovascular risk factor score (−0.61 SD, 95% CI −1.03 to −0.20) in young adulthood in multivariable-adjusted analyses including fitness. Associations to triglyceride, diastolic BP and the cardiovascular risk factor score remained with additional adjustment for waist circumference or BMI. Each 1 SD difference in isometric muscle strength in youth was significantly associated with 0.59 (95% CI 0.40 to 0.87) lower odds of general overweight/obesity in young adulthood (p=0.007) and was marginally associated with incident raised BP, raised triglyceride and low high-density lipoprotein cholesterol. Conclusions: This study suggests that greater isometric muscle strength in youth is associated with lower levels of cardiovascular risk factors in young adulthood independent of fitness, adiposity and other confounding factors.